Vulvar carcinoma in Fanconi Anaemia: A case report with review of literature - Vysakh Visweswaran; Hridya Jayamohanan; Anupama Rajanbabu; Keechilat Pavithran (Elsevier, 2021)
Fanconi anaemia is a rare autosomal recessive disorder associated with bone marrow failure and congenital malformations. The impaired DNA repair pathways in Fanconi anaemia predispose patients to a high risk of cancers of squamous cell origin, particularly in the head and neck region. Cancers of the vagina and vulva are rare in Fanconi anaemia. Here, we report a case of a 44-year-old female with Fanconi anaemia who developed an ulcerated lesion on the clitoris that extended into the labia majora. A biopsy of the lesion showed well-differentiated squamous cell carcinoma. The patient was treated with wide local excision of the vulval lesion. The patient developed neutropenia post-procedure but recovered in one week time. We have followed up the patient regularly since the procedure. No further issues have been detected to date.